2017
DOI: 10.1161/atvbaha.116.308524
|View full text |Cite
|
Sign up to set email alerts
|

Plasmin Cleaves Von Willebrand Factor at K1491-R1492 in the A1–A2 Linker Region in a Shear- and Glycan-Dependent Manner In Vitro

Abstract: Improved understanding of the plasmin-VWF interaction offers exciting opportunities to develop novel adjunctive therapies for the treatment of refractory thrombotic thrombocytopenic purpura.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 74 publications
1
33
0
1
Order By: Relevance
“…Finally, VWF plays a critical role in primary hemostasis and acts as a carrier for procoagulant FVIII. While the protein is known to be cleaved by the fibrinolytic enzyme plasmin, it is less clear whether the protein has a role in modulating the fibrinolytic process. In one study, there was no correlation between the plasma clot lysis time and VWF levels .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, VWF plays a critical role in primary hemostasis and acts as a carrier for procoagulant FVIII. While the protein is known to be cleaved by the fibrinolytic enzyme plasmin, it is less clear whether the protein has a role in modulating the fibrinolytic process. In one study, there was no correlation between the plasma clot lysis time and VWF levels .…”
Section: Discussionmentioning
confidence: 99%
“…In normal plasma, VWF multimeric composition is regulated by the metalloprotease ADAMTS13 (A Disintegrin And Metalloproteinase with ThromboSpondin type‐1 repeats) which cleaves a specific scissile bond (Tyr 1605‐Met 1606) within the VWF A2 domain (Sadler, ). In addition to ADAMTS13, recent studies have suggested that other plasma proteases, including plasmin, can also cleave VWF multimers (Brophy et al , ).…”
Section: Vwf Biosynthesis Structure and Functionmentioning
confidence: 99%
“…The majority of the N‐ and O‐glycan chains of VWF are capped by terminal sialic acid residues (Canis et al , , ) (Fig B). This sialylation modulates the susceptibility of VWF to proteolysis (McGrath et al , ; Brophy et al , ), and also plays a major role in regulating VWF clearance (Fig B). Enzymatic removal of sialic acid residues from VWF markedly reduces plasma half‐life (Sodetz et al , ; Stoddart et al , ; O'Sullivan et al , ; Ward et al , ).…”
Section: Vwf Glycans and Enhanced Clearancementioning
confidence: 99%
“…Different enzymes (including thrombin, plasmin, cathepsin G, neutrophil elastase, proteinase 3, matrix metalloproteinase 9, and granzyme M and B) have been associated with the regulation of VWF and platelet interaction. 44 Recent studies have also shown that plasmin can degrade VWF in microthrombi and break platelet-VWF complexes in vitro, 66,67 as well as stimulate ADAMTS13 activity in plasma. 68 In addition, recent work has demonstrated the interaction ULVWF multimers and the activation of the alternative pathway of complement, as well as the interactions of the complement system and the cleavage of ULVWF multimers.…”
Section: Future Directionsmentioning
confidence: 99%